2020
DOI: 10.1007/s12671-020-01487-3
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness Training is Associated with Changes in Alpha-Theta Cross-Frequency Dynamics During Meditation

Abstract: Ethics approval. The study was approved by the Singhealth Centralized Institutional Review Board and was conducted in accordance with the ethical standards of the 1964 Helsinki declaration and its later amendments.Consent. All participants provided written informed consent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 68 publications
2
27
0
Order By: Relevance
“…The overall reduction, rather than specific to the DMN, in gamma EEG-FC was reported during the transition from resting state to an active task (Berkovich-Ohana et al, 2014) or during meditation compared to rest (Faber et al, 2004) in experienced meditators. On the other hand, studies focusing on naïve practitioners before and after canonical mindfulness programs (e.g., MBSR) or shorter meditation protocols showed modulations of the theta and alpha bands following the training, while they did not report alterations of gamma bands (Lee et al, 2018b;Rodriguez-larios et al, 2020) In accordance with the later studies, we didn't find modulation in gamma bands but only in theta and alpha bands.…”
Section: 2supporting
confidence: 86%
“…The overall reduction, rather than specific to the DMN, in gamma EEG-FC was reported during the transition from resting state to an active task (Berkovich-Ohana et al, 2014) or during meditation compared to rest (Faber et al, 2004) in experienced meditators. On the other hand, studies focusing on naïve practitioners before and after canonical mindfulness programs (e.g., MBSR) or shorter meditation protocols showed modulations of the theta and alpha bands following the training, while they did not report alterations of gamma bands (Lee et al, 2018b;Rodriguez-larios et al, 2020) In accordance with the later studies, we didn't find modulation in gamma bands but only in theta and alpha bands.…”
Section: 2supporting
confidence: 86%
“…In addition to the analysis of amplitude in the EEG theta-alpha range (4-14Hz), we adopted a cross-frequency approach in which power modulations are analysed and interpreted as changes in the frequency architecture that influence the interaction between different brain rhythms (Rodriguez-Larios, Faber, et al, 2020;Rodriguez-Larios, Wong, et al, 2020;Rodriguez-Larios & Alaerts, 2019). This analytical approach is based on a recent theory positing that modulations in the center frequency of different brain rhythms determine crossfrequency communication (Klimesch, 2013(Klimesch, , 2018.…”
Section: Discussionmentioning
confidence: 99%
“…In the same line, it was shown that an 8week mindfulness training in novices (hours of practice and attendance to a mindfulness course) was associated with reduced alpha:theta phase synchrony / harmonicity during focused attention meditation (Rodriguez-Larios, Wong, et al, 2020). Since meditation training has been associated with reduced mind wandering during meditation practice (Brandmeyer & Delorme, 2018), it was postulated that the observed reductions in transient alpha-theta phase synchrony / harmonicity are reflective of a reduction in mind wandering episodes (Rodriguez-Larios, Faber, et al, 2020;Rodriguez-Larios, Wong, et al, 2020). In this way, it can be anticipated that, due to the putative role of alpha and theta rhythms in memory and executive control (Akiyama et al, 2017;de Vries et al, 2020;Rodriguez-Larios & Alaerts, 2019;Schack et al, 2005), a certain degree of alpha-theta phase synchrony is necessary for the generation of mind wandering episodes, as these would require the integration between memory and executive components of cognition (Kam & Handy, 2014;Smallwood & Schooler, 2006).…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations